Implementation and comparative study of control strategies for an isolated DFIG based WECS - N. Bouchiba; A. Barkia; L. Chrifi Alaoui; S. Drid; MBA. Kammoun (2017)
Nowadays, a global interest for renewable energy sources has been growing intensely. In particular, a wind energy has become the most popular. In case of autonomous systems, wind energy conversion system (WECS) based on a double fed induction generator (DFIG) is widely used. In this paper, in order to control the stand-alone system outputs under wind speed and load variations, three kinds of nonlinear control strategies have been proposed, applied and compared, such as: Classical PI controller, Back-Stepping and Sliding Mode controllers. A series of experiments have been conducted to evaluate and to compare the developed controllers’ dynamic performances under load demand and speed variations. The design and the implementation of different control strategies to a 1.5kW doubly fed induction machine is carried out using a dSpace DS1104 card based on MATLAB/Simulink environment …